Perubahan Warna Resin Akrilik untuk Basis Gigi Tiruan dan Mahkota Jaket Akibat Jus Apel - Devi Rianti; Elly Munadziroh (Faculty of Dentistry, Universitas Indonesia, 2015)
This laboratory experiment studied the apple juice solution effect towards the color changes of acrylic resin denture base material and jacket crown. The study conducted by immersing 26 mm diameter and 0.4 mm thick heat cured acrylic plate samples in apple juice solution for 7, 14, and 28 days exercises, 10 samples used for each exercise. An optical spectrometer, a BPY-47 type photocell, and a digital microvoltage were used for the color changes observation. Statistical analysis used Oneway Anova and HSD with 0.05 significant level. The result showed the denture base material and jacket crown acrylica resin color changes after 7, 14, 28 days of immersion.